Evaluation of a Triple-Helical Peptide with Quenched Fluorophores for Optical Imaging of MMP-2 and MMP-9 Proteolytic Activity - Zhang, Xuan (Molecules, 2014)
Matrix metalloproteinases (MMP) 2 and 9, the gelatinases, have consistently been associated with tumor progression. The development of gelatinase-specific probes will be critical for identifying in vivo gelatinoic activity to understand the molecular role of the gelatinases in tumor development. Recently, a self-assembling homotrimeric triple-helical peptide (THP), incorporating a sequence from type V collagen, with high substrate specificity to the gelatinases has been developed. To determine whether this THP would be suitable for imaging protease activity, 5-carboxyfluorescein (5FAM) was conjugated, resulting in 5FAM(3)-THP and 5FAM(6)-THP, which were quenched up to 50%. 5FAM(6)-THP hydrolysis by MMP-2 and MMP-9 displayed k(cat)/K(M) values of 1.5 × 10(4) and 5.4 × 10(3) M(−1) s(−1), respectively. Additionally 5FAM(6)-THP visualized gelatinase activity in gelatinase positive HT-1080 cells, but not in gelatinase negative MCF-7 cells. Furthermore, the fluorescence in the HT-1080 cells was greatly attenuated by the addition of a MMP-2 and MMP-9 inhibitor, SB-3CT, indicating that the observed fluorescence release was mediated by gelatinase proteolysis and not non-specific proteolysis of the THPs. These results demonstrate that THPs fully substituted with fluorophores maintain their substrate specificity to the gelatinases in human cancer cells and may be useful in in vivo molecular imaging of gelatinase activity.